1996
DOI: 10.1016/0014-5793(96)00776-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐nuclease activity of the single‐chain ribosome‐inactivating proteins dianthin 30, saporin 6 and gelonin

Abstract: The single-chain ribosome-inactivating proteins (scRIPs) The so-RIPs asparin 1, dianthin 30, gelonin, momordin, PAP-S identified and mapped in pBR322.(pokeweed antiviral protein from Phytolacca americana seeds) and saporin 6 were highly purified as described previously [15]. HPLCpurified saporin 6, whose specific N-glycosidase activity had been Agarose and acrylamide/bis-acrylamide for gel electrophoresis were to the A-chains of ricin and related toxins [2], which are purchased from Clontech Laboratories, Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…These include Tyr 72 , Tyr 120 , Glu 176 , Arg 179 , and Trp 208 , which have been proposed to be present in the active site and play an important role in the catalysis (21). The role of two other invariant residues, Tyr 16 and Arg 24 , proposed to be important for structural stability of ricin (33), has also been studied. These residues were mutated to alanine to generate seven single mutants, Y16A, R24A, Y72A, Y120A, E176A, R179A, and W208A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include Tyr 72 , Tyr 120 , Glu 176 , Arg 179 , and Trp 208 , which have been proposed to be present in the active site and play an important role in the catalysis (21). The role of two other invariant residues, Tyr 16 and Arg 24 , proposed to be important for structural stability of ricin (33), has also been studied. These residues were mutated to alanine to generate seven single mutants, Y16A, R24A, Y72A, Y120A, E176A, R179A, and W208A.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the codons for the invariant residues Tyr 16 and Arg 24 were also mutated to that for alanine. All of the mutations were carried out by oligonucleotide-mediated site-directed mutagenesis (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a number of studies have demonstrated specific DNAse-like activity of RIPs, including SAP, as evidenced by DNA fragmentation. 13,14 Such DNA damage, characterized by micronuclei formation and the appearance of cytosolic oligonucleosomes, might play a role in the induction of apoptosis upon cell exposure to the toxin and contribute to target cell killing.…”
mentioning
confidence: 99%
“…A type II RIP consists of an A chain, functionally equivalent to a type I RIP, which is attached to a sugarbinding B chain (for review, see Mehta and Boston, 1998;Tumer et al, 1999;Nielsen and Boston, 2001). Besides RNA N-glycosidase activity, some RIPs have ribonuclease, DNase, DNA glycosylase, and apurinic/apyrimidic lyase activities (Li et al, 1991;Roncuzzi and Gasperi-Campani, 1996;Nicolas et al, 1997Nicolas et al, , 1998Nicolas et al, , 2000Hudak et al, 2000). In addition, RIPs from Trichosanthes kirilowii cell cultures have been demonstrated to possess chitinase activity (Remi Shih et al, 1997).…”
mentioning
confidence: 99%